PENGALAMAN MAHASISWA PROGRAM STUDI PROFESI NERS DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Raiman Parlindungan Situmorang; Evelyn Hemme Tambunan (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
ABSTRACTLearning structure of the professional ners program is based on clinical practice. However, this could not be fulfilled due to the Covid-19 pandemic where online learning has taken place. This study aimed to explore the professional ners students’ experience of online learning during Covid-19 pandemic. The study design used was descriptive phenomenology to explore the experience of nine participants through in-depth interviews. The participants were selected using purposive sampling with the inclusion criteria: professional ners students who were exposed to online learning, enrolled in second semester 2019/2020 and odd semester 2020/2021 and over 20 years old. The data were analyzed using qualitative content analysis. There were two categories of experiences that consisted of impeding and promoting experiences. The impeding experience category has 4 sub categories and supporting experience has 6 sub categories. Impeding and supporting experience has become a description of the experience of nurse profession students in online learning. ABSTRAK Struktur pembelajaran program studi profesi ners didasarkan pada praktik klinis. Namun, hal tersebut tidak dapat terpenuhi karena adanya pandemi Covid-19 dimana pembelajaran online telah berlangsung. Penelitian ini bertujuan untuk menggali pengalaman mahasiswa profesi ners dalam pembelajaran online di masa pandemi Covid-19. Desain penelitian yang digunakan adalah deskriptif fenomenologi untuk menggali pengalaman sembilan partisipan melalui wawancara mendalam. Partisipan dipilih secara purposive sampling dengan kriteria inklusi: mahasiswa profesi ners yang terpapar pembelajaran online, terdaftar pada semester II tahun akademik 2019/2020 dan semester gasal tahun akademik 2020/2021 dan berusia di atas 20 tahun. Analisis data menggunakan analisis isi kualitatif. Terdapat dua kategori pengalaman yang terdiri dari pengalaman yang menghambat dan pengalaman yang mendukung. Kategori pengalaman yang menghambat terdiri dari 4 sub kategori dan pengalaman yang mendukung terdiri dari 6 sub kategori. Pengalaman yang menghambat dan mendukung menjadi gambaran pengalaman mahasiswa profesi ners dalam pembelajaran online.